Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1017/s0013091502000974
|View full text |Cite
|
Sign up to set email alerts
|

Countable Versus Uncountable Ranks in Infinite Semigroups of Transformations and Relations

Abstract: The relative rank rank(S : A) of a subset A of a semigroup S is the minimum cardinality of a set B such that A ∪ B = S. It follows from a result of Sierpiński that, if X is infinite, the relative rank of a subset of the full transformation semigroup T X is either uncountable or at most 2. A similar result holds for the semigroup B X of binary relations on X.A subset S of T N is dominated (by U ) if there exists a countable subset U of T N with the property that for each σ in S there exists µ in U such that iσ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…Sierpiński [15] showed that any countable set of maps from X to X is contained in a 2-generated subsemigroup of T X . An alternative proof of this was given by Banach [1]; see also [8]. An immediate corollary of this result is that the relative rank of a subset of T X is either uncountable or at most two.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Sierpiński [15] showed that any countable set of maps from X to X is contained in a 2-generated subsemigroup of T X . An alternative proof of this was given by Banach [1]; see also [8]. An immediate corollary of this result is that the relative rank of a subset of T X is either uncountable or at most two.…”
Section: Introductionmentioning
confidence: 94%
“…The corresponding result, that any countable set of permutations is contained in a 2-generated subgroup of S X , was given some years later in [3]. The analogues of these results in the semigroup of all binary relations, the semigroup of all partial maps, and the symmetric inverse semigroup were proven in [8].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, a classical result in the field, proved by Sierpiński, states that every countable set of mappings from an infinite set X to itself can be generated using two such mappings; see [1], [7] or [12]. The semigroup of all mappings from X to X is denoted by T X .…”
Section: Introductionmentioning
confidence: 99%
“…In [5], to mention another interesting result, it has been shown that whenever G ⊆ S X then rank(S X : G) is 0, 1 or uncountable. Slight modifications of Banach's proof of Sierpiński's result can be used to prove analogous results for binary relations, partial mappings, and partial bijections of infinite sets; see [7].…”
Section: Introductionmentioning
confidence: 99%